Focusing on the process of research: Embedding reflexivity for gender-transformative action - Lopez, Diana E.; Bailey, Arwen; Osei-Amponsah, Charity; Nchanji, Eileen Bogweh; Cullen, Beth; Debevec, Liza; Ludwig, David; Portocarrero, Ana; Rietveld, Anne; Wong, Franz; Farnworth, Cathy Rozel (2024)
AUDIENCE: This document is designed to help gender researchers who want to make the processes of their research more reflexive, critical and gender transformative.